Association of vaccine policy with virus infection and awareness of hepatitis B in Fujian, China - Li-Fang Huang; Zhi-Qiang Lin; Xiu-Hui Yang; Hai-Rong Zhang; Fu-Zhen Wang; Feng Wang; Jiang-Nan Wu; Yong Zhou (Taylor & Francis Group, 2022)
China has regulated its hepatitis B vaccination policy. However, data on the prevalence of hepatitis B virus (HBV) infection have not been updated since 2014. In addition, the impact of the policy on awareness of hepatitis B is limited, especially in Fujian Province where HBV infection is highly prevalent. We conducted a sero-epidemiological survey in five national monitoring counties to address these concerns. A total of 5,873 subjects were included and classified into four birth cohorts according to the policy time nodes (1981, 1992, and 2002). The HBsAg carrier rate for the general population was 8.6% (95% confidence interval [CI]: 7.9-9.3). Compared with those born before 1981, adjusted odds ratios (OR) for HBV infection were 0.51 (95% CI: 0.43-0.62), 0.10 (0.08-0.12), and 0.015 (0.01-0.023) among the 1981-1991, 1992-2001, and ≥2002 birth cohorts, respectively; while the OR was 1.26 (1.00-1.57), 0.39 (0.26-0.58), and 0.019 (0.006-0.06) for HBsAg carriage, respectively. Among the 4865 residents aged ≥15 years, hepatitis B awareness has been declining since the introduction of the hepatitis B vaccine into the immunization program (β = −0.25, SE = 0.08, P = .001, and β = −0.20, SE = 0.08, P = .017 for 1992-2001 and ≥2002 birth cohort, respectively). This decline was obvious for the initiation time of the first dose of the hepatitis B vaccine. Although the hepatitis B vaccination policies have helped reduce the infection, the awareness has declined. More measures on the target population are warranted to improve the public's awareness of hepatitis B vaccination in the context of great achievements.